Can loss of agency and oppositional perturbation associated with antidepressant monotherapy and low-fidelity psychological treatment dilute the benefits of guideline-consistent depression treatment at the population level?. Issue 1 (2020) - Ormel, Johan; Bosker, Fokko J.; Hollon, Steven D.; Ruhe, Henricus G.
Abstract: Despite major expansions of evidence-based treatments of common mental disorders in recent decades, especially antidepressant medication, the point prevalence of depression has not decreased; instead it probably increased in young adults. We question whether antidepressants (AD)-monotherapy and low-fidelity-to-guideline psychological treatment (PT) might have no effect or even adverse effects in some patients and contexts that dilute the benefits of treatment at the population level, making it harder for population-based studies to detect treatment-driven prevalence reductions. Randomized Clinical Trial (RCT)s have not identified these effects because AD-monotherapy and low-fidelity PT are uncommon in RCTs where treatment protocols are specified and carefully monitored, unlike treatment in real-world settings. Second, RCTs may have missed the bigger picture of ultimate outcomes due to too short follow-ups. We elaborate two mechanisms through which AD-monotherapy and low-fidelity PT could produce adverse effects on long-term illness course. Both mechanisms are speculative and we outline how to test.